Gender Differences in Children's Antibiotic Use and Adherence - Blandhol, Christine; Sautmann, Anja (World Bank, Washington, DC, 2021)
Using in-home health records for 1,763 children in Mali, this paper examines gender differences in the uptake and duration of treatment with antibiotics. The detailed data provide a window into parents’ day-to-day decisions while accounting for symptoms. There are no gender differences in starting treatment, but boys are over 10 percentage points more likely to complete a course of antibiotics than girls. This difference is driven by families with an educated household head. An explanation may be that (male) household heads are less involved in caring for girls, so that benefits from education that lead to better care accrue overproportionally to boys.